(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
Vocal art plays a pivotal role in the education and upbringing of youth, contributing to their emotional, intellectual, and social development. This article explores the significance of vocal art in youth education, with a particular focus on Uzbek Shashmaqom, a classical vocal tradition. Shashmaqom, a unique blend of melody, rhythm, and poetry, has been a cornerstone of Uzbekistan’s cultural heritage and provides a rich medium for fostering aesthetic appreciation, spiritual growth, and national identity among young people. The research emphasizes how vocal art, especially traditional forms like Shashmaqom, can shape youth in areas such as emotional expression, cultural awareness, and moral values. The article discusses practical approaches to incorporating vocal art into educational settings, and highlights its potential to develop creativity, discipline, and a sense of community among young learners.